Surto de Diarréia por Rotavírus - Sampaio Tavares Timenetsky, Maria do Carmo; Compagnoli Carmona, Rita de Cássia; Guadagnucci Morillo, Simone; Faria Costa, Fernanda; Cilli, Audrey; Bernardes Borges, Daniele; Guiducci, Raquel; de Paula Eduardo, Maria Bernadete; Katsuya, Elizabeth Marie (BEPA. Boletim Epidemiológico Paulista, 2004)